Process Study, Simulation, and Optimization of the Direct Conversion of Biomass to Ethyl Levulinate - Woloszyn, Joanne (Université d'Ottawa / University of Ottawa, 2023)
Lignocellulosic biomass is a promising alternative to non-renewable fossil fuel resources for the sustainable production of fuels and chemicals. Levulinic acid (LA) is considered to be a versatile platform chemical which can be derived from biomass and further upgraded to high-value products like levulinate esters. In this work, the direct chemical conversion of lignocellulosic biomass to ethyl levulinate (EL) through LA was studied in collaboration with Gascon Biomass Research Inc. in an effort to valorize their surplus of lignocellulosic feedstock obtained from biomass recycling activities. A novel one-pot, biphasic, acid-catalyzed hydrolysis-esterification process developed by Prof. Tom Baker's lab (uOttawa Chemistry) was used. Kinetic analyses of the overall reaction pathway and major reaction steps were performed to investigate the effect of reaction conditions such as time, temperature, alcohol concentration, and catalyst concentration and evaluate the kinetic and thermodynamic parameters. Reactions were well modeled by power law rate equations with applicability of the Arrhenius expression and exhibited nearly first-order dependence with respect to each of the corresponding reactants and catalyst, as expected. Kinetic studies of LA esterification to various levulinate esters showed that the reaction is endothermic, endergonic, non-spontaneous, and non-rate-limiting. Increased alcohol alkyl chain length and branching reduced the thermodynamic favourability of LA esterification, likely due to steric effects. Process considerations such as reactor pressure, LA and EL partitioning, solvent:feedstock ratio, solvent recycling, and alternative feedstocks were investigated through various lab-scale studies and simulation case studies with UniSim® Design. The results of experimental studies informed the development of a preliminary potential process flow diagram consisting of eleven batch slurry reactors under agitation in parallel. The product streams feed into a continuous separation process composed of flash vessels and distillation columns to separate and purify the various products, intermediates, unconsumed reactants, and recoverable catalyst and solvent. This work ultimately informs decisions regarding future pilot-scale experiments, process design, and optimization for the envisioned large-scale biorefinery to produce EL.
Keywords: Biomass; Cellulose; Esterification; Ethyl levulinate; Levulinate ester; Levulinic acid; One-pot process; Reaction kinetics; Scale-up; Simulation; Thermodynamics